A new Early Cretaceous nerineoid gastropod from Argentina and its palaeobiogeographic and palaeoecological implications - Cataldo, Cecilia Soledad (2013)
A new species of nerineoid gastropod, Eunerinea mendozana, is described from the top of the Agrio Formation, Lower Cretaceous, at Lomas Bayas, Mendoza Province, west-central Argentina. The significance of this record lies in that it extends the Early Cretaceous distribution of the genus to the Southern Hemisphere and also may point to the occurrence of subtropical conditions in the northern part of the Neuquén Basin close to the Hauterivian/Barremian boundary. Individuals of E. mendozana are found forming large monospecific assemblages immersed in carbonate sediments. The relationships of E. mendozana with other South American Early Cretaceous nerineoids are considered, together  with a reevaluation of some of those records.